2007
DOI: 10.1007/s12011-007-0047-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nanoanatase TiO2 on Photosynthesis of Spinach Chloroplasts Under Different Light Illumination

Abstract: With a photocatalyzed characteristic, nanoanatase TiO2 under light could cause an oxidation-reduction reaction. Our studies had proved that nano-TiO2 could promote photosynthesis and greatly improve spinach growth. However, the mechanism of nano-TiO2 on promoting conversion from light energy to electron energy and from electron energy to active chemistry energy remains largely unclear. In this study, we report that the electron transfer, oxygen evolution, and photophosphorylation of chloroplast (Chl) from nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(70 citation statements)
references
References 12 publications
4
66
0
Order By: Relevance
“…TiO2-NPs protect the chloroplast from excessive light by augmenting the activity of antioxidant enzymes . Similarly, Lei et al (2007) as well as Monica and Cremonini (2009) found that TiO2-NPs increased photosynthesis and plant growth in spinach and enhanced absorption and transmission of solar energy to electron energy and chemical active energy. They also found that TiO2-NPs entered the chloroplast and was transferred in the photosynthetic electron transport chain to create NADP+, was reduced to NADPH, and coupled to photophosphorylation and transformed electron energy to ATP.…”
Section: Discussionmentioning
confidence: 88%
“…TiO2-NPs protect the chloroplast from excessive light by augmenting the activity of antioxidant enzymes . Similarly, Lei et al (2007) as well as Monica and Cremonini (2009) found that TiO2-NPs increased photosynthesis and plant growth in spinach and enhanced absorption and transmission of solar energy to electron energy and chemical active energy. They also found that TiO2-NPs entered the chloroplast and was transferred in the photosynthetic electron transport chain to create NADP+, was reduced to NADPH, and coupled to photophosphorylation and transformed electron energy to ATP.…”
Section: Discussionmentioning
confidence: 88%
“…Addition of 0.25% nano-TiO 2 (rutile) stimulated oxygen evolution rate in spinach chloroplasts, improved chloroplast coupling and enhanced activities of Mg 2+ -ATPase and chloroplast coupling factor I CF 1 -ATPase on the thylakoid membranes [70] and nano-TiO 2 (rutile) protected chloroplasts from aging for long-time illumination [71]. Great increase of the electron transfer, oxygen evolution, and photophosphorylation was observed also in chloroplasts from nanoanatase-TiO 2 -treated spinach under visible light and ultraviolet light illumination [72]. Biomass accumulation of spinach (Spinacia oleracea) by TiO 2 NPs (by 60%) was also observed by Gao et al [73].…”
Section: Positive Effects Of Mnps On Plantsmentioning
confidence: 95%
“…Lu et al (2002) showed the productive effect of mixture of SiO 2 and TiO 2 nanoparticles in G. max with increase in water and fertilizer uptake capacity and stimulation of nitrate reductase and antioxidant activity. Studies demonstrating the effect of nano-TiO 2 in promoting photosynthesis and growth in spinach have also been conducted in which an increase in photosynthetic processes under both visible and ultraviolet light has been reported due to the pivotal role of TiO 2 (Lei et al 2007). Zheng et al (2005) reported that TiO 2 nanoparticles have increased 73 % dry weight, threefold higher photosynthetic rate, and 45 % increment in chlorophyll a after seed treatment in spinach.…”
Section: Nano-fertilizers and Plant Growthmentioning
confidence: 99%